Study of the Agreement of the Apnea-Hypopnea Index Measured Simultaneously by Pressure Transducer via Respiratory Polygraphy and by Thermistor via Polysomnography in Real Time with the Same Individuals - Bich-T; Minh Quach-Thieu; Bao-N; Duy Nguyen-Duc; Nguyen Tran-Hiep; Thao Nguyen-Thi; Yen-Linh; Anh Nguyen-Tuan; Tram Tang-; Toi Nguyen-Van; Sy Duong-Quy (MDPI AG, 2022)
Background: Obstructive sleep apnea (OSA) is a common disorder and can lead to many severe complications; however, the majority of patients remain undiagnosed. Although polysomnography (PSG) remains the gold standard of diagnosis, it is usually uncomfortable and costly for patients. Purpose: The study aims to assess the agreement of the AHI measured by polygraphy (PG) (Philips Alice NightOne) with that of polysomnography (Philips Alice PDx) simultaneously recorded in-lab. Methods: A total of 11 voluntary participants over 18 years old underwent one night of simultaneous PSG and PG recording in sleep laboratories. Studied parameters (AHI, OAI, CAI, MAI, and minSpO2) were analyzed and reported by the Philips Sleepware G3 software. PSG and PG results were scored by qualified staff. Results: In terms of AHI, the mean AHI derived from PG was different from that of PSG-7.78 and 2.37 events/h, respectively. A Bland-Altman analysis of the AHI on PSG versus PG showed a mean difference of 5.41; limits of agreement (equal to ±2 standard deviations) were from −6.74 to 17.56. The Bland-Altman analysis showed a slight difference between the two methods, with a mean difference of −0.12 events/h in CAI, 1.35 events/h in OAI, and 0.42 events/h in MAI. Conclusions: In the population with a low suspicion of OSA, the PG showed a low agreement with the simultaneous PSG in the sleep lab. Therefore, PG should only be used as a screening method. Further studies with sufficient sensors in the expanded populations of OSA are needed.